Análise da confiabilidade, mantenabilidade e disponibilidade do oscilador do molde de uma máquina de lingotamento contínuo - Albani Junior, Severino (2017)
The challenges encountered in the steel market require companies to continually strive for excellence within a context of cost optimization, with an acceptable risk to the desired performance. In this context, Reliability Engineering makes possible the application of different methodologies, with emphasis on Reliability, Maintainability and Availability (RAM Analysis). This work seeks to define a methodology to use RAM Analysis in ArcelorMittal Tubarão assets to understand the variables that influence asset availability and direct efforts to maximize production. As an application, the proposed methodology was used in the Mold Oscillator of a Continuous Casting Machine and allowed to know the factors that influence the reliability and maintainability of this system, as well as to define adequate control actions. The application of the RAM Analysis reached the expected objectives and proved to be a strategic tool to define the maintenance tasks and design adequacy for the assertive decision making.